Dynamics of Sex and Age Correlation of Eurasian Woodcock (Scolopax rusticola L.) During Spring Migration in Hungary - Attila Bende; Sándor Faragó; Richárd László; Viktória Csanády; István Fekete; Tibor Pecsics; László Bozó (Birds, 2025)
Based on samples collected in the framework of the Eurasian Woodcock Bagging Program in Hungary between 2010 and 2019, we investigated the spring migration of Eurasian Woodcock by age class and sex. The dynamical properties of each year’s trajectory are represented using Gaussian smoothing. The models were used to determine the peak of the migration by sex and age in each year. In the comparative analysis by sex, an ARIMA regression model was used as a time-series analysis, which showed that there was a strong positive correlation between the migration of females and males in each year, which indicates that there is no statistically verifiable time difference in the migration pattern of each sex. We found a positive correlation in the same ARIMA model for each year of migration, which indicates that there is no statistically verifiable difference in the spring migration of males and females of the same age groups in Hungary. This study also demonstrates that there is a sharp ratio shift in the spring migration in favour of males. This significant imbalance can be explained by the selective hunting during spring roding, which is of particular importance for the sustainable utilisation of the species.